Imagining societies through discourses on educational equality: A cross-cultural analysis of Finnish and Swedish upper secondary curricula from 1970 to the 2010s. (May 2019) - Lappalainen, Sirpa; Nylund, Mattias; Rosvall, Per-Åke
Educational equality has been a central tenet framing educational policy in Nordic welfare states and stimulating school reforms in the 1960s and 1970s. However, the conceptualisation of equality has fluctuated, reflecting the changing economic and political climate within which policy statements have been made. In this article, we analyse policy and curriculum documents relating to upper secondary education from the 1970s to the 2010s in two Nordic countries. Drawing on Nancy Fraser's theorisation of different forms of injustice, we focus on the aims and goals that are attached to the concept of educational equality, analysing how ideas about society and educational equality have changed over these decades. Our analysis suggests that over this period there have been quite dramatic shifts in how equality is conceptualised, inter alia shifting from a focus on economic inequalities to questions of sexuality and ethnicity. Furthermore, ambitions about tackling economic inequality have largely been replaced with ambitions about promoting employability, which is particularly visible in the curriculum of vocational upper secondary education. The Finnish general upper secondary education (GUS) curriculum has gone against the tide. In the 1970s the GUS curriculum had the most conservative tone in terms of equality, whereas the current curriculum requires an agentic stance against discrimination and a critical stance towards marketisation.